Consumo de plantas alimentícias não convencionais (PANC) pelos estudantes do 5º ano da escola municipal Pedro Álvares Cabral do Município de Santa Helena - PR - Dillenburger, Sandra Marli (2024)
Non-Conventional Food Plants (NCFP) are plants that have great food and nutritional potential and can strengthen the Food Security of the population, related to the Sustainable Development Goals (SDGs). The objective of this study was to identify the knowledge about NCFP by the family and the 5th year students of the Pedro Álvares Cabral Municipal School of the Municipality of Santa Helena - PR. The methodology of the study is based on bibliographic research with a descriptive approach. Regarding the research procedures, it is categorized as a qualitative-quantitative study, carried out through the application of two questionnaires. The first was applied to the students and the second to their parents/guardians. An interview was conducted with the school cafeteria ladies, addressing questions relevant to the NCFP topic. The results obtained showed that NCFP are known and consumed by students in their meals. They also demonstrated to have knowledge about some species such as Azedinha, Ora-pronóbis, Peixinho-da-horta, Almeirão-roxo, Serralha, Bertalha, Cará-gizzard, Taioba and Batata Doce leaf, they are interested in cultivating NCFP in their residences. The survey of the students' parents revealed that they try to maintain a healthy diet by including vegetables in the diet due to the perception that they are a source of nutrients, contribute to the prevention of diseases and promote the consumption of fresh foods. Specifically regarding NCFP, they affirm that they know them, consume them and use them to enrich the family diet. In an interview with the lunch ladies, it was clear that they use NCFP to prepare the foods served to students in the school environment and are very well accepted by them, despite not knowing specifically what ingredients NCFP contains. These findings allow us to perceive that there is an opening for the deepening and development of more comprehensive activities aimed at raising awareness, dissemination and multiplication of technical information, forms of use and preparation and, finally, the redefinition of the use of NCFP from respect. and valorization of social and cultural aspects from the rescue of the community's food identity.